Dnmt3b regulates DUX4 expression in a tissue-dependent manner in transgenic D4Z4 mice - Linde F. Bouwman; Bianca den Hamer; Elwin P. Verveer; Lente J. S. Lerink; Yvonne D. Krom; Silvère M. van der Maarel; Jessica C. de Greef (Skeletal Muscle, 2020)
Abstract Background Facioscapulohumeral muscular dystrophy (FSHD) is a skeletal muscle disorder that is caused by derepression of the transcription factor DUX4 in skeletal muscle cells. Apart from SMCHD1, DNMT3B was recently identified as a disease gene and disease modifier in FSHD. However, the exact role of DNMT3B at the D4Z4 repeat array remains unknown. Methods To determine the role of Dnmt3b on DUX4 repression, hemizygous mice with a FSHD-sized D4Z4 repeat array (D4Z4-2.5 mice) were cross-bred with mice carrying an in-frame exon skipping mutation in Dnmt3b (Dnmt3bMommeD14 mice). Additionally, siRNA knockdowns of Dnmt3b were performed in mouse embryonic stem cells (mESCs) derived from the D4Z4-2.5 mouse model. Results In mESCs derived from D4Z4-2.5 mice, Dnmt3b was enriched at the D4Z4 repeat array and DUX4 transcript levels were upregulated after a knockdown of Dnmt3b. In D4Z4-2.5/Dnmt3bMommeD14 mice, Dnmt3b protein levels were reduced; however, DUX4 RNA levels in skeletal muscles were not enhanced and no pathology was observed. Interestingly, D4Z4-2.5/Dnmt3bMommeD14 mice showed a loss of DNA methylation at the D4Z4 repeat array and significantly higher DUX4 transcript levels in secondary lymphoid organs. As these lymphoid organs seem to be more sensitive to epigenetic modifiers of the D4Z4 repeat array, different immune cell populations were quantified in the spleen and inguinal lymph nodes of D4Z4-2.5 mice crossed with Dnmt3bMommeD14 mice or Smchd1MommeD1 mice. Only in D4Z4-2.5/Smchd1MommeD1 mice the immune cell populations were disturbed. Conclusions Our data demonstrates that loss of Dnmt3b results in derepression of DUX4 in lymphoid tissues and mESCs but not in myogenic cells of D4Z4-2.5/Dnmt3bMommeD14 mice. In addition, the Smchd1MommeD1 variant seems to have a more potent role in DUX4 derepression. Our studies suggest that the immune system is particularly but differentially sensitive to D4Z4 chromatin modifiers which may provide a molecular basis for the yet underexplored immune involvement in FSHD.